2001
DOI: 10.1038/35093011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of mechanosensory transduction

Abstract: Mechanotransduction - a cell's conversion of a mechanical stimulus into an electrical signal - reveals vital features of an organism's environment. From hair cells and skin mechanoreceptors in vertebrates, to bristle receptors in flies and touch receptors in worms, mechanically sensitive cells are essential in the life of an organism. The scarcity of these cells and the uniqueness of their transduction mechanisms have conspired to slow molecular characterization of the ensembles that carry out mechanotransduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
482
0
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 645 publications
(493 citation statements)
references
References 96 publications
4
482
0
7
Order By: Relevance
“…In order to enable a broad range of functions, such as cell motility, transport across ion-channels, or the formation of active enzymatic pockets, living organisms rely on mechanochemical transduction schemes that are based on a multitude of non-covalent interactions. 1,10 Non-covalent interactions have also emerged as a useful design tool for stimuli-responsive functional polymers. 11 Notable examples include mechanochromic blends containing selfassembled excimer-forming dyes that can be dispersed upon mechanical deformation, 12 healable polymers based on supramolecular motifs, which are presumed to dissociate upon application of excessive mechanical force, 13 and the mechanochemically activated dissociation of coordination polymers, which are useful for mechanically activated catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…In order to enable a broad range of functions, such as cell motility, transport across ion-channels, or the formation of active enzymatic pockets, living organisms rely on mechanochemical transduction schemes that are based on a multitude of non-covalent interactions. 1,10 Non-covalent interactions have also emerged as a useful design tool for stimuli-responsive functional polymers. 11 Notable examples include mechanochromic blends containing selfassembled excimer-forming dyes that can be dispersed upon mechanical deformation, 12 healable polymers based on supramolecular motifs, which are presumed to dissociate upon application of excessive mechanical force, 13 and the mechanochemically activated dissociation of coordination polymers, which are useful for mechanically activated catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanotransduction concerns the cellular responses to a variety of mechanical stimuli [1][2][3][4][5][6][7]. Specialized mechano-sensitive cells, such as hair cells in the inner ear or dorsal root ganglion touch receptors, are equipped with highly sensitive transduction channel complexes.…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, we investigated in this study whether an agerelated decline in afferent sensitivity correlates with altered expression of membrane channel proteins. We focused on the thermosensitive ion channels in the transient receptor potential (TRP) family and the tetrototoxin resistant sodium channels since these channels are involved in the generation and transmission of impulse trains in response to mechanical and thermal stimuli [19,23]. Effects of aging on electrical membrane properties (EMP) of mouse DRG neurons in culture have indicated that neurons of aged animals (22-23-month old) exhibit decreased electrical excitability and increased action potential duration compared to younger animals (2-3.5-month old) [33].…”
Section: Introductionmentioning
confidence: 99%